Increasing Student Engagement in Islamic Jurisprudence Learning through SHARIA Board Game Media in Elementary Schools - Vinanda Istikha; Agus Fakhruddin; Achmad Faqihuddin (Universitas Muhammadiyah Mataram, 2025)
This study aims to increase student engagement in Islamic Jurisprudence learning through the SHARIA Board Game in elementary schools. The research employed a descriptive qualitative approach supported by simple quantitative descriptive data, using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The participants consisted of one Islamic Religious Education teacher and 15 fourth-grade students. Data were obtained through observation, interviews, documentation, questionnaires, and test scores, and were analyzed using thematic analysis following Miles and Huberman’s (1994) model, including data reduction, data display, and conclusion drawing. The findings showed that the average student score increased from 70.77 to 80.67 (13.99%), and learning completeness improved from 46.15% to 73.33%. The SHARIA Board Game also strengthened student engagement across four dimensions: cognitive, behavioral, social, and spiritual. Students became more active, motivated, and collaborative during learning activities. Theoretically, this study contributes to Islamic Religious Education by demonstrating that game-based learning can transform abstract fiqh concepts into meaningful and contextual learning experiences. Practically, the SHARIA Board Game offers an effective, low-cost, non-digital learning alternative that can be implemented in elementary schools to enhance motivation, participation, and understanding of worship practices.